The Influence of Pregnant Women's Knowledge Level on High Risk in Pregnancy at PONEK RSU Cut Meutia - Hafsah Usman; Elvita; Ernita (Lembaga Pengembangan Kinerja Dosen, 2025)
High-risk pregnancy is one of the leading causes of increased maternal and infant morbidity and mortality. Pregnant women's knowledge of healthy pregnancy and danger signs plays a crucial role in preventing and reducing these risks. This study aims to determine the effect of pregnant women's knowledge level on high-risk pregnancy at the Emergency Obstetric and Neonatal Care (PONEK) unit of Cut Meutia General Hospital. This research employed a quantitative design with a cross-sectional approach. The sample consisted of 46 pregnant women selected through purposive sampling. Data were collected using questionnaires and medical record observations. The data were analyzed using the Chi-Square test with a significance level of α = 0.05. The results showed that most pregnant women with low knowledge experienced high-risk pregnancies (75%). The Chi-Square test revealed a significant relationship between knowledge level and the incidence of high-risk pregnancy (p = 0.001). Thus, there is a significant effect of pregnant women's knowledge level on the risk of high-risk pregnancy. Continuous educational efforts by health professionals are needed to improve maternal knowledge and reduce the incidence of high-risk pregnancies.